Marine Organisms with Anti-Amyloid Effect Through Their Role as BACE1 Inhibitors for Preventive Effort in Alzheimer’s Disease: A Literature Review - Putra, Made Raditya Arhya; Saputri, Legis Ocktaviana; Wicaksono, Teguh Budi; Nugraha, Kadek Nandita; Putri, Ajeng Ayu; Salsabila, Rika Kamila; Fidelia, Puspa Zalika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Alzheimer’s Disease (AD) is a gradually worsening neurodegenerative condition characterized by the build-up of beta-amyloid proteins, resulting in a decline in cognitive abilities. β-site amyloid precursor protein cleaving enzyme-1 (BACE1) is known to play a role in the formation of beta-amyloid plaques. Thus, theoretically, inhibiting BACE1 can potentially prevent and slow down the accumulation of these plaques. This study is a literature review that compiles data from various research examining the inhibitory effects of compounds from marine organisms on the BACE1 enzyme. A comprehensive analysis was conducted on the available literature to evaluate the potential of these compounds. 19 marine organisms and 40 compounds were identified with low IC50 values, five compounds with notably low IC50 values were identified: (1) 8,8’-Bieckol [1.62 µM] from Ecklonia cava, (2) Phlorofucofuroeckol A [2.13 µM] and (3a) Dieckol [2.21 µM] from Eisenia bicyclis, (4) bis-(2,3,6-tribromo-4,5-dihydroxybenzyl) ether [2.32 µM] from Symphyocladia latiuscula, (3b) another Dieckol [2.34 µM] also from Ecklonia cava and (5) Heparan sulfate [2.89 µM] from Portunus pelagicus. These findings underscore the therapeutic potential of marine compounds as BACE1 inhibitors for AD. However, further research is needed to explore their bioavailability and clinical efficacy for practical application in preventing and treating Alzheimer’s Disease.